Genome-wide association scan of neuropathic pain symptoms post total joint replacement highlights a variant in the protein-kinase C gene - Warner, Sophie C.; van Meurs, Joyce B.J.; Schiphof, Dieuwke; Bierma-Zeinstra, Sita M.; Hofman, Albert; Uitterlinden, Andre G.; Richardson, Helen; Jenkins, Wendy; Doherty, Michael; Valdes, Ana M. (Nature Publishing Group, 2017)
Neuropathic pain-like joint symptoms (NP) are seen in a proportion of individuals diagnosed with osteoarthritis (OA) and post total joint replacement (TJR). In this study, we performed a genome-wide association study (GWAS) using NP as defined by the painDETECT questionnaire (score >12 indicating possible NP) in 613 post-TJR participants recruited from Nottinghamshire (UK). The prevalence of possible NP was 17.8%. The top four hits from the GWAS and two other biologically relevant single-nucleotide polymorphisms (SNPs) were replicated in individuals with OA and post TJR from an independent study in the same area (N=908) and in individuals from the Rotterdam Study (N=212). Three of these SNPs showed effect sizes in the same direction as in the GWAS results in both replication cohorts. The strongest association upon meta-analysis of a recessive model was for the variant allele in rs887797 mapping to the protein kinase C alpha (PRKCA) gene odds ratio (OR)possNP=2.41 (95% CI 1.74–3.34, P=1.29 × 10−7). This SNP has been found to be associated with multiple sclerosis and encodes a functional variant affecting splicing and expression of the PRKCA gene. The PRKCA gene has been associated with long-term potentiation, synaptic plasticity, chronic pain and memory in the literature, making this a biologically relevant finding.